2013
DOI: 10.1039/c3tc30964a
|View full text |Cite
|
Sign up to set email alerts
|

ZnAl2O4 as a potential sensor: variation of luminescence with thermal history

Abstract: ZnAl 2 O 4 spinel powders were prepared using the Pechini or co-precipitation synthetic route and were then treated at different temperatures (600-1350 °C). These powders were characterised by X-ray diffraction, scanning electron microscopy (SEM), diffuse reflectance and luminescence measurements. SEM investigations and the X-ray patterns showed that the spinel crystallite size was dependent on the synthetic route and the treatment temperature. In addition, the structural evolution was investigated by Rietveld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 61 publications
7
67
0
Order By: Relevance
“…Aguilar et al [18] [29][30][31] after calcination at 600 ℃. This is in agreement with previous studies by Cornu et al [20]. They also found that the amorphous precursor, obtained from the Pechini or co-precipitation synthetic route, transformed into ZnAl 2 O 4 spinel phase after heat treatment at 600 ℃.…”
Section: Xrd Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Aguilar et al [18] [29][30][31] after calcination at 600 ℃. This is in agreement with previous studies by Cornu et al [20]. They also found that the amorphous precursor, obtained from the Pechini or co-precipitation synthetic route, transformed into ZnAl 2 O 4 spinel phase after heat treatment at 600 ℃.…”
Section: Xrd Analysissupporting
confidence: 93%
“…The single phase NiAl 2 O 4 spinel powders were obtained at 1400 (unmilled powders) and 1100 ˚C (15 h milled powders) ; however, their optical properties have not been examined. Cornu et al [20] studied the luminescence properties of ZnAl 2 O 4 particles which were prepared using the Pechini or co-precipitation synthetic route and treated at different temperatures between 600 and 1350 ℃. It was found that the transformation of amorphous precursor to ZnAl 2 O 4 spinel phase occurred after heat treatment at 600 ℃ and various luminescence emissions linked to the presence of defects in the matrix structure.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel structure metal-oxide (AB 2 O 4 ) is a kind of important functional semiconductor materials, which have attracted extensive attention due to its unique crystal structure, special properties and broad application prospect in the fields, such as catalysts, catalytic carriers, high-temperature ceramics, optical materials, sensors and dielectric materials [1][2][3][4][5][6][7], etc. In the formula AB 2 O 4 , A represents the tetrahedral position occupied by bivalent metal cations, and the tetrahedral gap formed by four oxygen ions, while B position represents the octahedral position occupied by the trivalent metal cations, and the octahedral void formed by six oxygen ions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The emission and absorption characteristics of these defects are very sensitive to the local bonding environment and microstructure of the material and therefore its thermal history. Perhaps the earliest work of this type was that of Feist 19,20 , but subsequent important research has also been performed by Eilers 21 and Cornu 22 . In these methods, after a thermal event, a laser or optical parametric oscillator is used to excite carriers to the upper defect levels where a subsequent fluorescent event emits photons.…”
Section: Thermal History Sensing: Prior Artmentioning
confidence: 99%